Negatively Skewed Locomotor Activity Is Related to Autistic Traits and Behavioral Problems in Typically Developing Children and Those With Autism Spectrum Disorders - Ogino, Kazuo; Takahashi, Hidetoshi; Nakamura, Toru; Kim, Jinhyuk; Kikuchi, Hiroe; Nakahachi, Takayuki; Ebishima, Ken; Yoshiuchi, Kazuhiro; Ando, Tetsuya; Sumiyoshi, Tomiki; Stickley, Andrew; Yamamoto, Yoshiharu; et al. (Frontiers in Human Neuroscience, 2018)
An important objective for researchers and clinicians is to gain a better understanding of the factors that underlie autism spectrum disorders (ASD). It is possible that investigating objective and quantitative behavioral phenotypes and their relationship to clinical characteristics, such as autistic traits and other emotional/behavioral problems, might facilitate this process. Given this, in the current study we examined the link between locomotor dynamics and clinical characteristics, including autistic traits and emotional/behavioral problems, in children with ASD (n = 14) and typically developing children (TD, n = 13). A watch-type actigraph was used to continuously measure locomotor activity which was assessed in terms of mean activity levels and the skewness of activity. Parents assessed quantitative autistic traits using the Japanese version of the Social Responsiveness Scale (SRS) and emotional and behavioral problems using the Japanese version of the Strengths and Difficulties Questionnaire (SDQ). Results showed that among all children, all-day activity was more negatively skewed, suggesting sporadic large all-day “troughs” in activity and was significantly correlated with the SRS social awareness subscale score (rho=-0.446, p=0.038). In addition, the more negatively skewed daytime locomotor activity was associated with the SDQ Hyperactivity Inattention subscale score (rho=-0.493, p=0.020). The results of this study indicate that investigating locomotor dynamics may provide one way to increase understanding of the neurophysiological mechanisms underlying the clinical characteristics of ASD.